Thirst Traps and Quick Cuts: The Effects of TikTok “Edits” on Evaluations of Politicians - Kevin Munger; Valerie Li (Social Media + Society)
TikTok and the associated technologies for recording and editing short-form video constitute a large and growing portion of online communication. Previous modalities of social media, including static images and especially text, engendered significant attention to the facticity of the communication: was a statement true or false? Did an event actually take place? For a certain genre of stylized, highly edited short-form video, this is beside the point—which is to produce a compelling video that portrays a prominent figure in a particular light. We conduct an experiment to evaluate whether “edits” of prominent politicians can change voter perceptions. We find that “thirst trap” edits cause an increase in perceptions of politician attractiveness and that “badass” edits improve overall evaluations of Donald Trump (but not Joe Biden). Descriptively, we present a distribution of the evaluations of the attractiveness of Trump, Biden, Bernie Sanders, and Robert F. Kennedy Jr (“RFK”), demonstrating significant variation.